2018
DOI: 10.1371/journal.pone.0206055
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome profiling of transgenic potato plants provides insights into variability caused by plant transformation

Abstract: Crop genetic engineering involves transformation in which transgenic plants are regenerated through tissue culture manipulations that can elicit somaclonal variation due to mutations, translocations, and/or epigenetic alterations. Here, we report on alterations in the transcriptome in a panel of transgenic potato plants engineered to be herbicide resistant. Using an inbred diploid potato clone (DMRH S5 28–5), ten single-insert transgenic lines derived from independent Agrobacterium-mediated transformation even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 57 publications
2
8
0
Order By: Relevance
“…Overall, the AdDHN1 transcript abundance did not correlate with the enhanced freezing tolerance or the accumulation of soluble sugars, in particular for the OE 32.5 line, indicating a possible post-transcriptional regulatory mechanism of the transgene. These findings are in agreement with the general presumption that there is no clear relationship between the transcript levels of overexpressed transgenes and the phenotypic effects observed in transgenic lines, which can vary from a strong positive to no significant correlation (Kerr et al, 2018; Ko et al, 2018). Based on these analyses, the six freezing-tolerant OE lines were selected for further analysis.…”
Section: Resultssupporting
confidence: 91%
“…Overall, the AdDHN1 transcript abundance did not correlate with the enhanced freezing tolerance or the accumulation of soluble sugars, in particular for the OE 32.5 line, indicating a possible post-transcriptional regulatory mechanism of the transgene. These findings are in agreement with the general presumption that there is no clear relationship between the transcript levels of overexpressed transgenes and the phenotypic effects observed in transgenic lines, which can vary from a strong positive to no significant correlation (Kerr et al, 2018; Ko et al, 2018). Based on these analyses, the six freezing-tolerant OE lines were selected for further analysis.…”
Section: Resultssupporting
confidence: 91%
“…However, nearly two thirds of these exonic mutations are not silent and could potentially affect protein function, secondary structure, etc. An analysis of changes to the epigenome, which is frequently connected with aberrant phenotypes of transformants, would likely be informative [ 7 , 17 , 88 ]. It is also possible that mobilization of transposable elements is responsible for some alteration in the transformants [ 89 , 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of tissue culture with transformation, these aberrant phenotypes can be a result of the inserted transgene itself. T-DNA from Agrobacterium preferentially integrates into transcriptionally active regions of the genome, and constructs used for transgenic transformation also often contain one or more strong enhancer and promoter elements which can alter transcriptional levels of genes or generate antisense transcripts [ 10 17 ]. Insertion of T-DNA sequences has also been shown to disrupt genome structure both on small and large scales, causing deletions, duplications, translocations, and transversion [ 18 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…They found that the genetic transformation process infrequently results in novel genetic variation, but single nucleotide substitution rates were similar between fast neutron and transformed plants. Transcriptomic variability caused by plant transformation in transgenic potato were studied and revealed not only transcription factors but also specific transcription factor binding sites were also enriched in promoter region of differentially expressed gene in transgenic lines (Ko et al 2018). In the present study, we did not prepare the negative control of transgenic soybean with empty vector transformation due to the incomprehensive considerations.…”
Section: Discussionmentioning
confidence: 87%
“…Previous studies have reported that transgenic plants are regenerated via tissue culture manipulations, which can elicit somaclonal variation due to mutations, transposable elements, and epigenetic alterations. In addition, T-DNA insertion can trigger some unintended effects such as position effects and chromosome translocations (Jiang et al 2011;Sabot et al 2011;Endo et al 2015;Anderson et al 2016;Ko et al 2018). By using next-generation sequencing b Volcano plots of DEGs detected in leaf, stem, root, and seed of transgenic soybean lines.…”
Section: Discussionmentioning
confidence: 99%